(3GdaNQ GdefjQ aj GdUdGI Ydi GdHTjQ GdfPjQs - (3YeQ Hf Ydj GddNej GdeGdcj GdGScfOQj GdaGcgGfj,J (B731 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG ddESdGe CeG HYO aEf ef CMH TjFkG CcKQ ef PcQg GdHGH GdChd ai Mce GdUdGI Ydjg Udi Gddg Ydjg hSde s
(3BNQgG (B:s
(3jfJgi HCKfGA GdHGH GdMGOi YTQ ajef GSJZGK Hg Ydjg GdSdGe aCZjK ai GdbOje hGdMOjK s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3gPg gi GdfSNI GdhMjOI hgfGc fSNI CNQi ePchQI ai eagQS LhJG HGSe BNQ jXf CfgG ef GdcJGH hef Ke UhQJ s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdESdGejs